Curricular reforms carried out in Ecuador: A Literature Review - Haro Chávez, Yadira (Revista Ecos de la Academia, 2025)
The process of curricular reforms in Ecuador is marked by the lack of knowledge among educational actors about the changes, challenges, and progress that its implementation implies. The aim of this research is to analyze the curricular proposals implemented in Ecuador from their inception in 1996 to the present. The review is documentary; it involves exploring, selecting, organizing, and analyzing the existing literature on this theme. The most significant results highlight that the different curricular reforms have made important contributions to the country’s quality education, providing essential curricular guidelines for contextualizing the educational process, moving from simply delivering content outlines to teachers to offering a competency-based curriculum. Currently, the Prioritized Curriculum is in force, emphasizing communication, mathematical, digital, and socio-emotional skills, along with curricular integrations. The benefits of its implementation fall on students, while the challenges and responsibilities fall on the managers and teachers. In conclusion, it is clear that each curricular reform proposed by the Ministry of Education since 1996 has represented progress, innovation and improvement quality, relevant, and contextualized education, capable of responding to a constantly changing world.
Keywords: curricular reforms; educational process; focus on competencies; quality education